Sexually transmitted diseases and male infertility in the Nigerian (2003)
Infection related infertility is common in Nigeria. The study was designed to evaluate the involvement of sexually transmitted diseases (STDs) in the pathogenesis of male infertility. One hundred and eighty-two male subjects aged 18-56 years were investigated-fertile (85), infertile (50), men with STDs (47). Semen was analysed according to WHO guidelines and appropriate statistical tests performed. Over 65% of subjects with STDs had gonorrhea and non-specific urethritis(NSU). More than two-thirds of STDs subjects (76.4%) were dyspermic and oligospermia was most frequently observed in infertile subjects (30%). Sperm count, percentage motility and morphology were significantly lower in infertile than fertile controls (P<0.001) while percentage motility was significantly lower in men with STDs than fertile controls (P = 0.005). Gonorrhea and NSU are still prevalent in the Nigerian society. STDs may cause infertility in the African male by reducing sperm motility and semen volume.